Serum albumin level as prognostic indicator of acute ischemic stroke in tertiary care hospital admitted patients - Dash, Prafulla Kumar; Behera, Smrutiranjan; Sahoo, Nirmal Chandra; Rattan, Roma; Tripathy, Saroj Kumar (International Journal of Advances in Medicine, 2020)
Background: Serum Albumin level is an important multifunctional protein in the blood for maintaining the normal permeability across vessel wall by osmotic gradient, in inhibiting platelet aggregation and in reducing blood viscosity. Serum albumin level as a novel parameter for predicting outcome and assessment of severity of coronary artery disease is established. Keeping in mind the scarcity of studies regarding albumin level in ischemic Cerebrovascular Accident (CVA), present study was undertaken to correlate serum albumin level with clinical outcome in acute ischemic stroke (AIS) patients. Methods: One hundred patients of diagnosed AIS were included in the study. Thorough clinical examination and risk factor profile assessment was done. Severity of stroke was assessed using National Institute of Health Stroke Scale (NIHSS) Score and then followed up to 1 week and 3 months post-admission with serum albumin level and assessment was done using modified Rankin Scale (mRS) score. Institutional ethics committee cleared the study. Results: In 100 patients with AIS, 58% were male and 42% were female. Mean age was 65±8.160. Motor weakness (85%) was the commonest presenting symptom. Around 75% of patients revealed infarction in middle cerebral artery (MCA) territory. Hypertension (HTN) (74%) was the most frequently associated comorbid condition. Patients with low serum albumin level at admission time were directly proportional to severity of stroke at presentation and poor clinical outcome. 1 week and 3 months follow up mean albumin level (g/dl) was 3.8±0.25 and 3.7±0.23 in patients with poor functional outcome respectively. Significant co-relation between mean serum albumin level and clinical outcome was observed. Conclusions: Serum albumin level is inversely correlated with severity of stroke at presentation and functional outcome in patients on follow up.